If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5-2t=-5t+2
We move all terms to the left:
5-2t-(-5t+2)=0
We get rid of parentheses
-2t+5t-2+5=0
We add all the numbers together, and all the variables
3t+3=0
We move all terms containing t to the left, all other terms to the right
3t=-3
t=-3/3
t=-1
| -2y=-4+8 | | 2p+18=34 | | 7x+x/2=22 | | 0=8x²+16x+8 | | 2x2=72 | | -8x+9=2(13-4x)-17 | | x1/6=4/18 | | 4=10-3g | | (n+1)²-n²=61 | | 2x-43=32-3x | | (x)(x)=289 | | -105-4x=50+x | | 3(2x+4)4x=10 | | x-1/6=4/18 | | 2/3+x=180 | | 1+13+16x=1234567890 | | h=35=15 | | x+0.5=15 | | (5x+2)/8=7 | | 54=3(2x+4) | | 9f+7-6=-5+6f | | -14m=-56 | | 2b-5=8b+1b= | | 84+b=(42*8)+9 | | X-2+7-4x=0 | | 6x+6=-16x-20-3x | | 7/10=z/15 | | 2x+4+3=54 | | 84+b=(84*8)+9 | | 5x-7-4x+7=0 | | -42-5x=-11x+18 | | 4^2x+3=1 |